Avaliação da aderência do consumidor em relação ao produto verde - Angelocci, Manna Ariente; da Silva, Dirceu; Putti, Fernando Ferrari [UNESP]; Reckziegel, Valmor; Fustaino, Joanna; Naves, Luciana de Paula; Fonseca, Leonardo da Silva (My University, 2016)
This work aims to study the involvement of consumer in green actions, with the choice of the type of product, green or not green, as green tack on shares. The work has as problem to verify adherence in green stocks and the acceptance of green product. Through a full factorial experiment design between 2×3 subjects, taking the product strands as green and non-green products and green marketing involvement (high, medium and low), a causal and quantitative research was conducted. The data gathering was conducted in the classroom, with the focus on a sample of 838 women that had proved a moisturizer in order to evaluate the noted quality of the product tasted. Then, the participants in the study filled a questionnaire, with grades 0-10, the Ecological Consciousness Scale with 26 items, including two cases of buying a moisturizer. As a result, an analysis of the involvement of participants in green actions was performed. This research is supposed to contribute to the understanding of green marketing and the development of new studies in the sector.
Consumer compliance evaluation with respect to the product green